Designing interoperable telehealth platforms: bridging IoT devices with cloud infrastructures. Issue 8 (13th September 2020) - Tsiouris, Kostas M.; Gatsios, Dimitrios; Tsakanikas, Vassilios; Pardalis, Athanasios A.; Kouris, Ioannis; Androutsou, Thelma; Tarousi, Marilena; Vujnovic Sedlar, Natasa; Somarakis, Iason; Mostajeran, Fariba; Filipovic, Nenad; op den Akker, Harm; et al.
ABSTRACT: A platform offering web technologies and interoperable components is proposed, allowing integration of different technologies into a robust system. Key modules are provided in home, to support integration of IoT devices, and in the cloud, offering centralised services and storage. Communication between the two is performed using the open FIWARE-Orion protocol. Data are not tied to methods and resources, so the platform can handle multiple types of requests and data formats. The platform is deployed in HOLOBALANCE, a tele-rehabilitation system for balance disorders, providing surrogate holographic physiotherapists, real time evaluations of task performance and cloud-based data analytics for personalised coaching.